Зміст і співвідношення правових принципів, спрямованих на забезпечення та захист прав і свобод громадян, засуджених до позбавлення волі в Україні - Почанська, О. С.; Pochanska, O. S.; ORCID: http://orcid.org/0000-0003-3953-8660 (Європейські перспективи. - 2020. - № 3. – С. 136-142, 2020)
Досліджено зміст і особливості правових принципів, які становлять основу нормативно-правового забезпечення прав і свобод громадян, засуджених до позбавлення волі в Україні. Уточнено поняття «правові принципи», визначено та надано загальну характеристику загальноправових та спеціальних норм-принципів, які складають систему правових гарантій прав та свобод громадян, засуджених до позбавлення волі.

It is noted that an effective mechanism for ensuring the rights and freedoms of citizens sentenced to imprisonment in Ukraine is the legal means (guarantees) of regulating the process of serving a criminal sentence in general, and defining and protecting the rights and freedoms of convicts as a key component of their legal status. The essence of the concept of “legal principles” is revealed. It is emphasized that the normative-legal guarantees of ensuring the rights and freedoms of the citizen, as provided by the norms of substantive and procedural law legal means to ensure their implementation, protection and defense, by their legal nature are enshrined, first of all, in the norms-principles. protection of human and civil rights and freedoms in the state. The system of general and special legal principles that form the basis of normative-legal guarantees of the rights and freedoms of citizens sentenced to imprisonment is determined. It is established that the basis of normative-legal guarantees of the rights and freedoms of citizens sentenced to imprisonment in Ukraine are such common law principles as: the rule of law, the principle of legality, the principle of humanism, the principle of equality, the principle of justice. The special norms-principles aimed at ensuring and protecting the rights and freedoms of convicted citizens include: the principle of public participation in the activities of penitentiary bodies and institutions; principles of differentiation and individualization of execution of punishments; the principle of combining criminal punishment with educational influence and a number of principles directly related to the application of criminal punishment in the form of imprisonment. The content and correlation of legal principles aimed at ensuring and protecting the rights and freedoms of citizens sentenced to imprisonment in Ukraine are analyzed.

Исследовано содержание и особенности правовых принципов, составляющих основу нормативно-правового обеспечения прав и свобод граждан, приговоренных к лишению свободы в Украине. Уточнено понятие «правовые принципы», определена и дана общая характеристика общеправовых и специальных норм-принципов, составляющих систему правовых гарантий прав и свобод граждан, приговоренных к лишению свободы.
Почанська, О. С. Зміст і співвідношення правових принципів, спрямованих на забезпечення та захист прав і свобод громадян, засуджених до позбавлення волі в Україні / Почанська Олена Сергіївна // Європейські перспективи. - 2020. - № 3. – С. 136-142. - DOI: 10.32782/EP.2020.3.20.
Keywords: Кримінально-виконавче право. Criminal and Executive Law. Уголовно-исполнительное право; Наукові публікації. Scientific publications. Научные публикации; Конституційне право. Constitutional Law. Конституционное право; Україна. Ukraine. Украина; засуджений до позбавлення волі; sentenced to imprisonment; осужден к лишению свободы; правові принципи; legal principles; правовые принципы; нормативно-правове забезпечення; regulatory and legal support; нормативно-правовое обеспечение; права і свободи; захист прав і свобод; protection of rights and freedoms; защита прав и свобод